2022
DOI: 10.3389/fphys.2022.852094
|View full text |Cite
|
Sign up to set email alerts
|

Core Muscle Activation With Foam Rolling and Static Planks

Abstract: The objective of this study was to compare the activation of the core (trunk) musculature during quadriceps and hamstrings foam rolling (FR) vs. prone and supine/reverse static planks to determine if FR is a viable means of training the core musculature. Using a randomized allocation, nine recreationally trained, young adults (18–26 years) performed two sets each of quadriceps and hamstrings FR as well as supine/reverse and prone static planks for 30-s each with 1-min rest between sets and 5-min rest between e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…This finding is consistent with previous study, which revealed that a decrease in muscle strength was correlated to an increase in muscle soreness (Konrad et al, 2022). In addition, VFR interventions might improve muscular endurance in the lower limbs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous study, which revealed that a decrease in muscle strength was correlated to an increase in muscle soreness (Konrad et al, 2022). In addition, VFR interventions might improve muscular endurance in the lower limbs.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in agility ability in our study may also be due to the fact that the subjects actively engaged in VFR of the quadriceps and hamstrings. The authors reported that the quadriceps foam rolling in a modified plank position and the hamstrings rolling position in a seated upright position on the floor both induce lower abdominal activity and upper lumbar erector spine activity, the quadriceps foam rolling inducing large magnitude greater lower abdominals activity than hamstrings rolling position, and no significantly different compared to the general prone static plank exercise (Zahiri et al., 2022). In addition, the authors reported that moderate‐ and high‐intensity running provided greater activation of the back stabilizer muscles (Behm et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…If FR is applied to the hamstrings, quadriceps, or calf muscles, a position related to a plank position must be taken. A previous study showed that the muscle activity (i.e., electromyography) of the core muscles with a plank or reverse plank position is similar to that with quadriceps and hamstrings FR, respectively [ 45 ]. Thus, it can be assumed that the participants in the eligible studies of this meta-analysis might have improved their performance, but in their core muscles rather than in the tested/treated muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential increase in performance in the contralateral limb, which has been shown by our analysis, was likely not based on the FR stimulus itself, but might have resulted from the plank position participants performed while rolling the triceps surae muscles (Kasahara et al 2022b ) or the thigh muscles (Hodgson et al 2018 ). Zahiri et al ( 2022 ) showed that the muscle activity (i.e., electromyography) of the core muscles during a plank or reverse plank position is similar to that with quadriceps and hamstrings FR, respectively. Prior studies have also reported co-activation of the lumbar/core and the dorsal thigh muscles, which are linked via connective tissue (Wilke et al 2016 ; Krause et al 2016 ), during frequently used physical tests aimed at mainly targeting the core muscles (Demoulin et al 2006 ; Champagne et al 2008 ; Gabriel et al 2022 ).…”
Section: Contralateral Effects Of Foam Rolling On Performance Parametersmentioning
confidence: 99%